The role of liquidity risk in augmenting firm value: lessons from savings and credit cooperatives in Kenya - Waitherero, Kariuki Florence; Muchina, Stephen; Macharia, Stephen (Goodwood Publishing, 2021)
Purpose: The study aimed to examine the interaction between liquidity risk and the firm's value among Kenyan SACCOs. Research methodology: This study adopted the positivism research philosophy and utilised both descriptive and causal research designs. The study targeted all the 164 licenced SACCOs in Kenya. A sample made up of 115 respondents was selected using a stratified random sampling method. The study utilized secondary data obtained from organization’s published financial statements. Analysis of data was done using descriptive statistics and inferential analysis. Results: The study results illustrated that value of the firm was positively correlated with liquidity risk which significantly and favourably impacted the firm value; (?=0.014577, P=0.001). Limitations: The analysis and conclusions reached in this study were limited to data gathered for the five-year duration between 2012 and 2016. Contribution: This study is useful to the management of SACCOs and the Kenyan government to understand better how financial risk management can improve their firms' value. The study adds to the existing knowledge of financial risk management and firm value. Keywords: Savings and credit cooperatives, Liquidity risk, Firm value